Moldova Financial Sector Assessment Program : Corporate Governance Review of the Moldovan Banking Sector - World Bank (Washington, DC, 2015)
The banking sector in Moldova is in the midst of structural changes with worrisome corporate governance issues at the core. Corporate governance is at the center of a stable and profitable banking sector which is essential to support economic growth and productivity. However, the banking system in Moldova suffers from critical governance weaknesses which the National Bank of Moldova (NBM) has been unable to effectively address. The illicit schemes used to gain control of the majority of the banking sector’s assets have involved raider attacks by unidentified individuals whose subsequent, de facto, related party transactions have caused the deterioration of bank balance sheets. The recent changes in controlling ownership have resulted in nontransparent appointments of board members and Chief Executive Officers (CEOs). This has led to substantial blurring of the roles and responsibilities of ownership, oversight (board), and management, resulting in no clear accountability. The legal and institutional corporate governance framework in Moldova is weak. Sound corporate governance is first and foremost dependent upon the motivations of owners and the resultant business culture they instill through their selection and appointment of board members. In Moldova, a few actors control the majority of the banking system. They demonstrate dubious motives by acting obscurely through others and through companies to own and control important banks. These actions create a system that is held captive to serve the needs and pleasures of a few at the expense of many: the depositors, general public, and ultimately, the taxpayer.